Disfagia e alterações emocionais - Bretan, Onivaldo [UNESP]; Henry, Maria Aparecida Coelho de Arruda [UNESP]; Kerr-Corrêa, Florence [UNESP] (My University, 1997)
Swallowing function may be impaired by a number of conditions involving primary or associated emotional distress. When psychogenic dysphagia is suspected, routine investigation using radiological and manometric examination is inappropriate. These cases demand an evaluation of the individual as a whole, interesting the disease as well as the patient's personal problems and concerns. Five cases of patients complaining of swallowing difficulty and showing concurrent emotional distress were studied. Four individuals were anxious and one was depressed. Because of our approach, a close medical-patient-relationship was established. Afterwards, an explanation about the normal swallowing mechanisms and the role of the emotions on it was provided. All patients showed improvement of the symptom in the following 24 hours. Dysphagia can be found in anxiety, depression and conversion hysteria, with high incidence in the urban population of the third world countries. However, several professionals are unaware of these disorders. Our results suggest that this plain approach is an useful tool in managing dysphagic patients and it has validity even in individuals bearing dysphagia due to comproved organic disease. The results also emphasize the importance of the medical patient relationship and the utility of a hollistic evaluation of the disease.
Dysphagia and emotional distress
Keywords: anxiety; depression; dysphagia; management; adult; aged; clinical article; doctor patient relation; emotional stress; human; male